Adsorption of U(VI) ion by modifiled chitosan flakes: optimization of process parameters and thermodynamic studies - Ho , Thi Yeu Ly; Nguyen , Mong Sinh (Nuclear Science and Technology, 2013)
The cross-linking chitosan modified by citric acid has been studied for sorption of U(VI) from aqueous solution in a bath system. The effects of parameters such as pH, initial U(VI) concentration, contact time and temperature on the sorption of U(VI) were analyzed using response surface methodology (RSM). The Minitab was used to conduct the regression analysis and the analysis of nvariance of the U(VI) adsorption by modified chitosan. The U(VI) concentration of 100 mg/L, pH 4.2, temperature of 313 K and contact time of 211 min were determined as optimum conditions for U(VI) adsorption by acid citric grafted chitosan (C-GCh). The maximum efficiency of U(VI) removal by CGCh was 97,35 % at the optimum sorption conditions. Thermodynamic parameters such as ΔG, ΔH, ΔS for U(VI) adsorption process in aqueous solution were also determined.